Rhapsody for the theatre - Badiou, Alain; Bosteels, Bruno; Puchner, Martin (London ; New York : Verso, 2013)
"Gathers most of Alain Badiou's writings on theatre, including ... reflections on his own art as a playwright and its relation to his work as a philosopher."--Page vii, Introduction.
Rhapsody for the theatre : a short philosophical treatise -- Theatre and philosophy -- The political destiny of theatre yesterday and today -- Notes on Jean-Paul Sartre's The condemned of Altona -- The Ahmed tetralogy -- Three questions to the author.
Prijevod djela: Rhapsodie pour le théâtre, Théâtre et philosophie, i drugih dijela A. Badioua
Bibliografija: str. 167-168.- Kazalo
Text in English.
Keywords: Badiou, Alain; Badiou, Alain; Theater -- Philosophy; Theater -- Philosophy; filozofija kazališta